An Overview on Principles for Energy Efficient Robot Locomotion - Kashiri, Navvab; Abate, Andy; Abram, Sabrina J.; Albu-Schaffer, Alin; Clary, Patrick J.; Daley, Monica; Faraji, Salman; Furnemont, Raphael; Garabini, Manolo; Geyer, Hartmut; Grabowski, Alena M.; Hurst, Jonathan; et al. (Frontiers in Robotics and AI, 2018)
Despite enhancements in the development of robotic systems, the economy of robots is far behind that of biological systems. This paper reviews recent advancements in development of legged robotic systems from different perspectives, to elucidate the current stage of robotics in terms of energy efficiency, and to highlight solutions progressing this criterion. It includes a review of various robotic actuators exploiting compliance in series and parallel for energy recycling, and discusses the importance of limb segmentation in design, dynamics analysis and locomotion control of legged robotic systems. A number of energetically-established control approaches are explored and compared with human behaviors/controls. Finally, a set of cutting-edge topics initiating new directions in locomotion is reported.